Investigation of flow-induced noise reduction in high-specific-speed centrifugal pumps using bionic blades - Yongxin Jin; Tao Cheng; Jie Fu; Guangtai Shi; Lei He (Scientific Reports)
Abstract To reduce the flow-induced noise of centrifugal pumps and reveal the noise source characteristics inside the pumps, this paper designs a bionic blade based on the “tubercle effect” of humpback whales. The noise reduction effect of the improved structure is verified through numerical simulations of the flow and acoustic fields of the prototype pump and bionic pump. Using the Ffowcs Williams–Hawkings equation and Powell vortex sound equation, the reasons for the noise reduction are explained from the perspective of pressure pulsation and sound source. The results indicate that the bionic blade has little impact on the hydraulic performance of the centrifugal pump but can achieve a maximum noise reduction of 2.53 dB. The main sources of centrifugal pump noise are the severe pressure pulsation caused by rotor–stator interaction and the sound source generated by the influence of velocity on vortices. The reduction in pressure pulsation intensity, sound source, sound source intensity, and sound source standard deviation are the main reasons the bionic pump has lower noise than the prototype pump. However, the relationship between the magnitude of pressure pulsation intensity and dipole noise amplitude is not simply linear. The total sound pressure level reduction effect caused by suppressing the pressure pulsation whose main frequency is the blade passing frequency is significantly larger than that caused by suppressing the pressure pulsation whose main frequency is the shaft frequency.